I Am Not Here, I Am Out Looking for Myself: Intergeneration Dialogues - Gutiérrez Rojas, Marisol (2016)
The article is an analytical review of a teaching experience sustained by an intergeneration conversation. First year students dialogue with three humanist: Ernesto Sábato, José Saramago and José Mujica, whose experience in the everyday life in science, literature and -politics allow us to -meditate, from the cognitive and affective point of view, about knowledge of himself and the others as substantial base - of a more human world, memory and support coexistence and the (in)utility Humanities. It also refers to the pedagogical mediation that propitiates an experience of active, collaborative and creative learning, ending in the creation of essays an a multimedia high quality student made products. This educommunicative experience is part of the activities related with the 2016 Declaration as the Year of public universities for Mother Earth and the Congress of Humanistic Education, Arts and Culture Studies.